Determinants, behaviour change techniques and pedagogical approaches used in secondary school-based food and nutrition programmes: a qualitative study of the SWITCH project - Anouk Mesch; Madelief Engels; Sanne Raghoebar; Laura H. H. Winkens; Judith Gulikers; Renate Wesselink; Annemien Haveman-Nies (BMC Public Health)
Abstract Background Food and nutrition programmes at secondary schools have the potential to improve public and planetary health, as they target a wide range of adolescents. Nevertheless, it is currently unclear what mechanisms are underlying such educational interventions in order to aim for behaviour change. This qualitative study therefore aims to identify determinants and behaviour change techniques (BCTs) incorporated in secondary school-based food and nutrition programmes. Better understanding of determinants and BCTs can identify points of improvements to facilitate long-term dietary behaviour change. Methods Fifteen online semi-structured interviews were conducted between November 2021 and January 2022 with representatives of 14 Dutch programmes, supplemented by a document analysis of scientific and grey literature related to the included programmes (e.g., evaluation reports, teacher manuals). Transcripts and literature were analysed deductively, using the terminology of Mechanisms of Action (MOAs) and the BCT Taxonomy v1, followed by an inductive coding phase. Results Determinants knowledge (n = 13), skills (n = 12), awareness (n = 9), and beliefs about consequences (n = 7) were identified most, as well as BCTs Knowledge transfer (n = 13), Natural consequences (n = 7) and Goals and planning (n = 5). Inductive coding led to the identification of pedagogical approaches that were considered important for successful delivery of programmes, such as the use of activating learning methods. Conclusions It seems promising for food and nutrition programmes at secondary schools to expand their current focus beyond knowledge and skills, to also target environmental, social and other essential individual determinants during adolescence which are now under-reported, such as identity. Moreover, our study revealed the importance for programmes to be tailored to adolescents’ worldviews and to stimulate adolescents to be actively involved.